New data on the terrestrial isopod fauna of Iran (Isopoda: Oniscidea) with the first description of the male of Schizidium golovatchi Schmalfuss, 1988 - Ghasem Kashani; B. Eshaghi; A. Abedini (Iranian journal of animal biosystematics, 2021)
In the present study, seven species of terrestrial isopods are reported from Iran for the first time. These include Platyarthrus schoblii Budde-Lund, 1885; Trichorhina tomentosa (Budde-Lund, 1893); Armadillo alievi Schmalfuss, 1990; A. officinalis Duméril, 1816; Armadillidium azerbaidzhanum Schmalfuss, 1990, A. nasatum Budde-Lund, 1885 and Schizidium golovatchi Schmalfuss, 1988. The male of the latter species is described for the first time and its diagnostic characters are illustrated. Sampling localities for the species are presented on a map.